PARADIGMA PENGAJARAN JARAK JAUH (PJJ) BAGI GURU SEKOLAH DASAR - Pohan, Sutan Saribumi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2020)
Teaching distance or interacting between teachers and students virtually for elementary school teachers is a job that requires its own energy, besides requiring computer media with internet networks also observe the ability of students to be able to fulfill the learning process online, so that between teachers and students there are those who feel that interacting virtually is also tiring to feel tense, some are showing strengths and strengths in carrying out the learning process virtually, so it must be done wholeheartedly. In a situation or a change the teacher will choose a number of strategies and passion to be able to master and modify and innovate in the teaching process so that students can understand and feel happy with the online learning model and assignments that are done at home. For distance learning teachers with no psychological interaction with students is like controlling a ship hit by a storm, on one hand the teacher can provide material online smoothly to students from economically capable groups because it is supported by computer media or the internet, on the other hand the teacher must serve manually and optimally to students who are less able and do not have online media. For teachers who work with computers will feel and realize that teachers will be connected by the millennial education world, therefore teachers need to develop their potential as adaptations to the demands of the times.The only way to do great work is to love what you do, (Steve Jobs).